Отсубстантивные имена действия с формантами отглагольных nomina actionis в современных русском и польском языках - Koriakowcewa , Elena (Slavia Centralis, 2020)
Denominative nomina actionis with formants of verbal nomina actionis in contemporary Russian and Polish